Comparative metabolism of the antiviral dimer 3'-azido-3'-deoxythymidine-P-2',3'-dideoxyinosine and the monomers zidovudine and didanosine by rat, monkey, and human hepatocytes. - Pan-Zhou, X R (1997)
AZT-P-ddI is an antiviral heterodimer composed of one molecule of 3'-azido-3'-deoxythymidine (AZT) and one molecule of 2',3'-dideoxyinosine (ddI) linked through their 5' positions by a phosphate bond. The metabolic fate of the dimer was studied with isolated rat, monkey, and human hepatocytes and was compared with that of its component monomers AZT and ddI. Upon incubation of double-labeled [14C]AZT-P-[3H]ddI in freshly isolated rat hepatocytes in suspension at a final concentration of 10 microM, the dimer was taken up intact by cells and then rapidly cleaved to AZT, AZT monophosphate, ddI, and ddI monophosphate. AZT and ddI so formed were then subject to their respective catabolisms. High-performance liquid chromatography analyses of the extracellular medium and cell extracts revealed the presence of unchanged dimer, AZT, 3'-azido-3'-deoxy-5'-beta-D-glucopyranosylthymidine (GAZT), 3'-amino-3'-deoxythymidine (AMT), ddI, and a previously unrecognized derivative of the dideoxyribose moiety of ddI, designated ddI-M. Trace extracellular but substantial intracellular levels of the glucuronide derivative of AMT (3'-amino-3'-deoxy-5'-beta-D-glucopyranosylthymidine [GAMT]) were also detected. Moreover, the extent of the formation of AMT, GAZT, and ddI-M from the dimer was markedly lower than that with AZT and ddI alone by the hepatocytes. With hepatocytes in primary culture obtained from rat, monkey, and human, large interspecies variations in the metabolism of AZT-P-ddI were observed. While GAZT and ddI-M, metabolites of AZT and ddI, respectively, as well as AZT 5'-monophosphate (MP) and ddI-MP were detected in the extracellular media of all species, AMT and GAMT were produced only by rat and monkey hepatocytes. No such metabolites were formed by human hepatocytes. The metabolic fate of the dimer by human hepatocytes was consistent with in vivo data recently obtained from human immunodeficiency virus-infected patients.